Does purchasing recognition help or hinder purchasing quality performance in developing market SMEs? Effects of resource conditions. Issue 5 (December 2021) - Essuman, Dominic; Anin, Emmanuel Kwabena; Muntaka, Abdul Samed
Abstract: Prior studies contend that top managers' ability to harness purchasing recognition to enhance purchasing quality performance is crucial for boosting competitive advantage. However, there are doubts about the universal benefits of purchasing recognition, particularly in developing market small and medium enterprises (SMEs). This research uses upper echelons theory (UET) to move the literature forward by suggesting that the purchasing recognition-purchasing quality performance link depends on varying conditions of financial resource and environmental munificence. Consistent with the study hypotheses, survey data from one hundred and thirty-eight SMEs in Ghana indicates that financial resource and environmental munificence positively moderate the relationship between purchasing recognition and purchasing quality performance. In particular, the study results show that, under low and high conditions of financial resource and environmental munificence, the link between purchasing recognition and purchasing quality performance is significantly negative and positive, respectively. Theoretical and practical implications alongside the limitations of the results are discussed. Highlights: Purchasing recognition may not always enhance purchasing quality performance. Financial resource amplifies the positive effect of purchasing recognition. Munificent context amplifies the positive effect of purchasing recognition.